Training needs of MADA’s Assistant Agriculture Officers (AAO) - Abdullah, Khalil (2016)
Rice is a staple food of Malaysia and rice industry is considered as a strategic industry which always gets special attention from the government. The industry is seriously regulated because of its social, political and economic importance. In 2009, apart from being the main source of food, it also provides the livelihood to 172,000 paddy farmers in the country. The rice production in Malaysia still below self-sufficiency level (SSL) which is about 72%. Over decades, a policy after a policy has been introduced by the government to improve the rice production. Because of that, a few authorities like Muda Agricultural Development Authority (MADA) were established just to focus on rice farming development. MADA also responsible as an extension agency which educates Muda’s farmers in managing their farm through their agriculture officers and disseminates the technology and information to them. This study was conducted to examine the training needs of Muda Agricultural Development Authority (MADA) officers in increasing their competency. The special objectives of this study were to examine the training need of MADA officers and to identify the relationship between the respondent’s demographic profile and training need. The questionnaires were designed and distributed to selected 163 respondents among agriculture officers. The respondents are focused on Assistant Agriculture Officer’s (AAO). The data were analyzed using Statistical Package for Social Science (SPSS) for the descriptive, ANOVA data and Borich Need Assessment. The respondents were found to have training needs in rank. The most important was selected and shown by the highest mean and the least important was shown by the lowest mean. Training needs selected from most preferred to the least preferred as follow, technical: non rice (4.40), development (4.23), language (4.23), farming practical (4.14), ICT (4.11), machinery (4.03), communication (3.92), demonstration method (3.91), motivation (3.91), farm visit (3.89), farm management (3.88), organization management (3.85), technical: non-rice (3.74), agricultural marketing (3.74), leadership (3.71), business (3.71), entrepreneurship (3.56), industry (3.54), drainage and irrigation management (3.54), agribusiness (3.51), civics (3.40) and foundation (3.33). Next, found that some training needs were needed by some AAOs of MADA, and some training needs were needed by some AAOs of MADA, while some training needs were not needed by AAOs. Found that technical: non-rice and machinery have significant difference between genders at 0.05 level of significance. The others 20 training needs there are no significant different between genders. Technical: non-rice is preferred by female with mean of 4.150. Next, machinery is more preferred by male by mean of 4.146. Furthermore, found that there are at least significant difference on demonstration method and agricultural marketing between years of experienced at 0.05 level of significance. The others 20 training needs there are no significant different between years of experienced. Demonstration method and agricultural marketing are more chose by those are have experienced more than 4 years. In conclusion, training needs should be done due to what have been selected by the respondents of AAOs of MADA in ranking from most preferred to the least preferred which are technical: rice, development, language, farming practical, ICT, machinery, communication, demonstration method, motivation, farm visit, farm management, organization management, technical: non-rice, agricultural marketing, leadership, business, entrepreneurship, industry, drainage and irrigation management, agribusiness, civics and foundation. The first listed should give more focus and last should be give less focus. The recommendation is among those 22 training needs 4 of them should be done separated training based on gender and years of experiences for cut cost and increase efficiency. Training on technical: non-rice and machinery can be separated based on gender which is training of technical: non-rice should be focused on by female and machinery should be focused male. Furthermore, demonstration method and agricultural marketing can be separated based on years of experiences which are demonstration method and agricultural marketing trainings should be focused on AAOs that have experiences more than 4 years working in MADA.